VolleyJump: Uma aplicação para a análise de saltos no voleibol de praia - Bandeira, Renan; Trinta, Fernando; Gomes, João; Maia, Marcio; Araripe, Alexandre (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2018)
Professional sports are increasingly dependents of technological resources given the remarkable level of competitiveness faced by high performance athletes. With such resources, it is possible to analyze matches, avoid mistakes that may be committed by the referee or even to analyze the athletes’ performance. One of these sports is beach volleyball, one of most popular sports in Brazil. In the past 12 years, the Brazilian volleyball teams has been always among the best teams in the world. The athletes’ performance during the jump movement is one of the main factors that one team needs to improve to be successful because it is the movement that is most performed during a volleyball match. There are some approaches that study the jump movement in order to calculate its height and give evidences to improve it. Nevertheless, these solutions are expensive and are not viable to athletes with no sponsorship. Having this in mind, this works presents VolleyJump, an application created to analyze beach volleyball athlete jumps using machine learning strategies to calculate the jump height and classify it as an attack or block jump. Results show that VolleyIoT makes possible to analyze athletes’ jumps using mobile devices sensors, helping them to focus on their trainning to improve its technique.